2015
DOI: 10.1007/s13280-015-0727-8
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural vulnerability over the Chinese Loess Plateau in response to climate change: Exposure, sensitivity, and adaptive capacity

Abstract: Understanding how the vulnerability of agricultural production to climate change can differ spatially has practical significance to sustainable management of agricultural systems worldwide. Accordingly, this study developed a conceptual framework to assess the agricultural vulnerability of 243 rural counties on the Chinese Loess Plateau. Indicators representing the climate/agriculture interface were selected to describe exposure and sensitivity, while stocks of certain capitals were used to describe adaptive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Cumulative vulnerability index (CVI) in this study was determined as the positive function of EI and SI, but negative function of ACI following Li et al (2015), as under:…”
Section: Cumulative Vulnerability Index (Cvi)mentioning
confidence: 99%
“…Cumulative vulnerability index (CVI) in this study was determined as the positive function of EI and SI, but negative function of ACI following Li et al (2015), as under:…”
Section: Cumulative Vulnerability Index (Cvi)mentioning
confidence: 99%
“…Wheat is the dominant crop in the Loess Plateau, accounting for 35% of the total planting area [1,2]. Dryland wheat production in Loess Plateau is highly dependent on the timing and extent of rainfall, whereas most of the precipitation is mainly concentrated during the summer fallow period.…”
Section: Introductionmentioning
confidence: 99%
“…In order to sustain agriculture industry, the Chinese government should take measures on environmental pollution and degradation, climate change and replace with new policies with the environment and ecology-friendly agricultural technologies. Li et al [6] reported that western China was the most vulnerable area, where climate sensitive dry land agriculture was the primary economic activity. The Loess Plateau is a home to an estimated population upwards of 108 million, of which more than 70% are reported to be living and working in agricultural areas.…”
Section: Resultsmentioning
confidence: 99%